(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2018)
The purpose of our study was the identification of spring wheat varieties resistant to cadmium, a priority pollutant in the East Kazakhstan region. The experiments were carried out in the condition of model environmental pollution on 14-day sprouts of various spring wheat varieties, that were grown on a nutrient mixture, containing 0.1 mM of CaSO4 and Cd ions at a concentration of 40 mg/l. Screening of spring wheat varieties under the conditions of the model experiment made it possible to identify resistant and sensitive genotypes. In terms of growth and accumulation of cadmium in the aboveground organs, the most resistant to cadmium spring wheat varieties are Samal and Kaiyr, the least resistant are the varieties Lutescens and Zhenis. In terms of growth and accumulation of cadmium in the roots, the most resistant varieties of spring wheat were Kazakhstan-15 and Kazakhstan Early, the most unstable – the variety Lutescens. Chlorophyll a is more sensitive to the action of cadmium ions than chlorophyll в. Cadmium-resistant varieties can be used in field studies of soil contamination with cadmium to identify promising forms that combine metal resistance with high yield and resistance to weather conditions.